2020
DOI: 10.12669/pjms.36.5.1647
|View full text |Cite
|
Sign up to set email alerts
|

Fetomaternal outcome in patients with placenta previa

Abstract: Objectives: To assess maternal and fetal morbidity associated with placenta previa and morbidly adherent placenta (MAP). Methods: All patients with placenta previa who delivered in services hospital from April 1, 2017 to March 31, 2019 were included. Maternal and fetal outcomes were compared amongst patients with placenta previa and MAP. Results: Total of 8002 patients delivered with 152 (1.9%)diagnosed as placenta previa and 56 (36.8%) amongst them had MAP. One hundred thirty-one out of One hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 18 publications
5
24
1
Order By: Relevance
“…Wasim et al [16] stated that fetal outcome was good in patients with MAP and placenta previa in our study with majority (73.2% vs 65.6%) delivering after 36 weeks with good APGAR and babies having birth weight ≥2.5kg and only three neonatal deaths due to prematurity.…”
Section: Fetal Outcomesupporting
confidence: 45%
See 1 more Smart Citation
“…Wasim et al [16] stated that fetal outcome was good in patients with MAP and placenta previa in our study with majority (73.2% vs 65.6%) delivering after 36 weeks with good APGAR and babies having birth weight ≥2.5kg and only three neonatal deaths due to prematurity.…”
Section: Fetal Outcomesupporting
confidence: 45%
“…It was significantly more among subjects with Emergency LSCS, APGAR score, NICU admission and duration of hospital stay > 10 days. Wasim et al [16] reported that low case fatality of 3% as only two patients died.…”
Section: Mortalitymentioning
confidence: 98%
“…The placenta previa (PP) is defined as placenta complete or partial covering the internal orifice of cervix (1), the prevalence of PP in obstetrics is about 0.3-1.5% (2). The PP is a major risk factor for severe postpartum hemorrhage (SPPH), which is the leading cause of maternal and neonate mortality and morbidity worldwide (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, the incidence of PP shows an increasing trend year by year with the increase of cesarean section rate, abortion rate, and uterine operations ( 2 4 ). The presence of PP can increase the risk of maternal hemorrhage in late pregnancy, during labor, and in the postpartum period, and in severe cases can lead to hemodynamic instability, reduced oxygen supply, and organ damage causing emergency unscheduled surgery requiring massive blood transfusion; it can also produce serious symptoms such as disseminated intravascular coagulation and multiple organ dysfunction syndrome, which are the main causes of maternal and perinatal death ( 5 , 6 ).…”
Section: Prefacementioning
confidence: 99%